Implementing TPM supported by 5S to improve the availability of an automotive production line - Ribeiro, I.M. (2020)
The maintenance management is a topic of strategic importance for automotive manufacturers. In fact, an effective maintenance process and a preventive maintenance (PM) procedure can significantly reduce the risk of equipment failures that can lead to downtime on the production lines. However, due to the complexity of an automotive production system, the risk of failure on a crucial piece of the production equipment cannot be entirely avoided. The study made in this paper aims at improving the availability of a critical production line through the total productive maintenance (TPM) methodology and supported by Lean Maintenance tools. An analysis is made of the initial condition of the line where the main problems are identified by employing several tools for this purpose, such as Mean Time between Failures (MTBF), Mean Time to Repair (MTTR), Overall Equipment Efficiency (OEE) and Availability (A). In response to the identified problems, an action plan is developed and implemented in order to find the root cause of the high number of malfunctions and faults in one of the line’s equipment with the use of 5S tools, visual management, and maintenance progress, as well as the development of a training program to increase operators’ skills. The results of such actions were positive as the line became more organized, the value of the MTBF increased, the MTTR value decreased, and consequently the overall availability increased.